Eosinophilic Granulomatous Polyangitiis- a hopeful outcome of a Sinister disease- a case report - Debasish Roychoudhury; Rammohan Gumpeni; Kenneth Sha (Cardiovascular Journal, 2024)
Eosinophilic myocarditis is a rare form of myocardial inflammation characterized by eosinophilic infiltration and often accompanied by eosinophilia. It can be fatal in in its initial presentation. Although the condition is rare, it’s quite variable in terms of clinical presentation and prognosis ranging from fulminant myocarditis to uneventful recovery. We present a case of a young female patient with eosinophilic myocarditis who had favorable outcome after treatment with steroid and immunosuppressive agents. Cardiovasc j 2024; 16(2): 102-104